2022
DOI: 10.3390/ijerph191610092
|View full text |Cite
|
Sign up to set email alerts
|

Total Mercury and Fatty Acids in Selected Fish Species on the Polish Market: A Risk to Human Health

Abstract: The muscles of lake trout (Salvelinus namaycush Walbaum, 1792), crucian carp (Carassius carassius Linnaeus, 1758), flounder (Platichthys flesus Linnaeus, 1758), gilthead seabream (Sparus aurata Linnaeus, 1758), mackerel (Scomber scombrus Linnaeus, 1758) and tench (Tinca tinca Linnaeus, 1758) were examined. The total mercury (THg) was processed using the Milestone DMA-80 and the fatty acids were analyzed using the 7890A Agilent Technologies chromatograph. The THg content in analyzed fish ranged from 0.024 (lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…0.42%, 0.52%, and 0.69% increases are observed in fisheries output if market size rises by 1% in the case of FEOLS, FMOLS, and DOLS, respectively. This finding was verified by Ewald et al (2022), Nielsen et al (2022), and Łuczyńska et al (2022) for European nations, Alsaleh and Abdul‐Rahim (2021, 2022a, 2022b) for EU developing countries which suggest that market efficiency boosts fisheries productivity. In the same way, the empirical results explain a negative connection between intellectual capital rights and fisheries productivity in EU13 developing nations.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…0.42%, 0.52%, and 0.69% increases are observed in fisheries output if market size rises by 1% in the case of FEOLS, FMOLS, and DOLS, respectively. This finding was verified by Ewald et al (2022), Nielsen et al (2022), and Łuczyńska et al (2022) for European nations, Alsaleh and Abdul‐Rahim (2021, 2022a, 2022b) for EU developing countries which suggest that market efficiency boosts fisheries productivity. In the same way, the empirical results explain a negative connection between intellectual capital rights and fisheries productivity in EU13 developing nations.…”
Section: Resultssupporting
confidence: 54%
“…The influence of market development on the expansion of the Asian fisheries sector was examined by Malto and Dumilag (2023), Shimose and Kanaiwa (2022), and Macusi et al (2022), who concluded that an efficient fisheries management plan is crucial to the sustainability of the fisheries market. Ewald et al (2022), Nielsen et al (2022), and Łuczyńska et al (2022) investigated the fish market development for sustainable development of seafood products in Europe, demonstrating how integrating domestic and international markets can promote the sustainable development of fisheries and the expansion of the fisheries market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The fatty acids EPA y DHA content were expressed in g·100 g −1 of edible fish muscles according to Eq. (3) [56] , [75] : where FA is the fatty acid (g·100 g −1 muscle of fish); P is the fatty acid percentage (% of total lipids); FC is the free-solvent oil content expressed in fresh weight (g·100 g −1 of fish muscle); C is the conversion factor, calculated according to Weihrauch et al [101] ; Yilmaz [106] , considering the total lipid (TL) content ( Eq. (4) ).…”
Section: Methodsmentioning
confidence: 99%
“… [54] ), which is converted to MeHg by bacterial activity [30] , [35] . MeHg is a toxic, stable organic compound that is consumed by marine microorganisms, and its concentration increases through the food chain up to higher trophic levels, affecting not only aquatic species but also reaching humans through the food web [25] , [56] . According to several studies, MeHg represents around 64–100% of total mercury (THg) content, depending on the size and age of the fish [105] .…”
Section: Introductionmentioning
confidence: 99%
“…A major concern is the ability of Hg to be easily transferred along trophic chains through bioaccumulation and biomagnification processes and then be accumulated in wildlife at high trophic levels [ 8 , 9 ]. In particular, in aquatic environments, its organic and highly toxic form, methylmercury (MeHg), is produced both in the water column and in sediments by certain sulfate-reducing bacteria and tends to be accumulated mainly in the tissues of aquatic organisms such as fish [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%